Design and Implementation of Tank Level Monitoring System Using Internet of Things - Heriyawan, Mohammad Sapta; Santiko, Tony; Pujianto, Erli (Universitas Dharma Wacana, 2025)
This study seeks to create and implement an IoT-based tank level monitoring system to rectify the inefficiencies associated with human sounding methods typically employed on ships. Manual measuring methods can lead to protracted processes and human errors, thereby affecting data precision and operational safety. This research addresses these restrictions by integrating an ESP32 microcontroller, HC-SR04 ultrasonic sensor, and the Blynk IoT platform to develop an automated monitoring solution that transmits real-time water level data to a mobile dashboard. The system was developed utilizing the Waterfall Model, which includes the phases of requirement analysis, system design, implementation, testing, and maintenance. The proposed system exhibited great accuracy within a range of 2–400 cm and maintained stable Wi-Fi connectivity without signal loss, achieved through iterative development and expert validation. The Blynk interface effectively provided real-time viewing of water height and volume. An analysis of user input revealed a favourable reaction, with an average rating of 3.8 on a 5-point scale, indicating system usability and efficacy. The results validate that the suggested IoT-based monitoring system provides a dependable, cost-effective, and scalable substitute for manual measurement, enhancing both operational efficiency and maritime technology education.